Analisis Kinerja Green Supply Chain Management Pada UMKM Batik Seni Pendopo - Rika Nurmitha; Tri Inda Fadhila Rahma; Budi Dharma (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
One of the world's most famous native Indonesian cultures is batik. A good batik industry must be able to produce superior batik according to market needs with quality standards, the environment, human rights and employment issues. Batik craftsmen have weak tools, use velvet chemicals, handle water and a high amount of water, and are inefficient in handling wax and other processing agents. Batik Seni Pendopo is one of the batik businesses that practices GSCM. Dokani Svetsini needs to manage mezimuzi kineria green manufacturing at Batik Seni Pendopo so that it can continue to operate its business, maintain the surrounding environment, and implement the proposed semparikan persang mezimuzi results consistently. This research uses a qualitative case study type, using the green SCOR and AHP methods. From the results of Mezurisi Ergirden, the performance value is 77.43, which means good. Of the 13 KPIs, there are several KPIs that have unsatisfactory performance, namely energy use, waste produced by % of products produced, production costs, installation costs, waste management, efficiency, stamping, batik canting. Improvements that are important in this business are minimizing the handling of electricity, handling raw materials for candle wax and water, managing candle wax for business income, modifying the management so that the cash that goes to Milan can be milled, and where farmers design and canting so that the production process is faster.